Development of Visual Art in Saudi Arabia: Case study from Saudi context (Architecture Image Studies, 2025)
This research investigates the factors and obstacles affecting the development of Visual Arts in Saudi Arabia, along with potential solutions. Using a qualitative, phenomenological approach, interviews were conducted with 18 visual artists and faculty members from Riyadh and Jeddah. The findings identify key hindering factors, including political issues (colonial legacy, closure of art centers), academic shortcomings (absence of specialized colleges and curricula), and societal-religious challenges (misconceptions about art). Artists face significant obstacles such as the high cost of materials, a lack of societal appreciation, and an absence of museums and galleries. To enhance the field, participants strongly recommended substantial governmental support through legislating supportive policies, establishing arts academies, cultural centers, and providing scholarships, complemented by social and economic initiatives to foster a conducive environment for artists.